STRATEGI DAKWAH NAHDLATUL ULAMA DAN MUHAMMADIYAH DALAM MENANGKAL RADIKALISME DI KABUPATEN BONDOWOSO - Ade Nurwahyudi; Ahidul Asror (Indonesian Journal of Islamic Communication, 2020)
The current radicalism movement has occurred in Indonesia. The emergence of this radical concept was caused by the existence of a group of Muslims who wants to purify religious teachings during the pre-independence period until now. In Bondowoso, this concept enters through children in elementary school (SD). from that incident, the two Islamic Community Organizations (Ormas) in Bondowoso; Nahdlatul Ulama and Muhammadiyah opposed, rejected the existence of this concept. This research is descriptive qualitative based on case studies using the method of selecting subjects and data collection techniques through observation, interviews and documentation. Based on the results of this research, it can be concluded that the preaching strategies of Nahdlatul Ulama and Muhammadiyah in counteracting radicalism in Bondowoso Regency are (1) both Nahdlatul Ulama and Muhammadiyah provide the understanding to all administrators related to radicalism. (2) Nahdlatul Ulama invites all components to be aware of radicalism movements at all levels, while Muhammadiyah through social media. (3) Nahdlatul Ulama held a Cadre Education for the Movement of Nahdlatul Ulama (PKPNU) and Muhammadiyah held regular studies. (4) Nahdlatul Ulama conducts Da'wah Cadre Training (PKD), Pancasila cadre training and Muhammadiyah conducts social da'wah. (5) Nahdlatul Ulama conducts recitation, seminars and Muhammadiyah through Friday sermons.